2021
DOI: 10.1016/j.esmoop.2021.100123
|View full text |Cite
|
Sign up to set email alerts
|

The systemic pro-inflammatory response: targeting the dangerous liaison between COVID-19 and cancer

Abstract: Inflammation is an established driver of severe SARS-CoV-2 infection and a mechanism linked to the increased susceptibility to fatal COVID-19 demonstrated by patients with cancer. As patients with cancer exhibit a higher level of inflammation compared to the general patient population, patients with cancer and COVID-19 may uniquely benefit from strategies targeted at overcoming the unrestrained pro-inflammatory response. Targeted and non-targeted anti-inflammatory therapies may prevent end-organ damage in SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 142 publications
0
4
0
2
Order By: Relevance
“…The mortality in our study was elevated in Se and Zn deficiency, in particular within the groups of obese, chronic cardiac disease, cancer and diabetes patients. These conditions confer an increased mortality risk in COVID-19, and are often associated with (sub-)clinical inflammation, again potentially closing a vicious self-amplifying cycle [54,55]. As cancer and chronic cardiac disease were associated with a higher mortality particularly in the Se-deficient patients, obesity was associated with a higher mortality in Zn-deficient patients and both Se-and Zn-deficiency conferred increased mortality risk in particular for diabetes patients, it is hypothesized that Se and Zn deficiency may aggravate the negative impact of cancer, obesity, chronic cardiac disease and diabetes on an adequate immune response in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality in our study was elevated in Se and Zn deficiency, in particular within the groups of obese, chronic cardiac disease, cancer and diabetes patients. These conditions confer an increased mortality risk in COVID-19, and are often associated with (sub-)clinical inflammation, again potentially closing a vicious self-amplifying cycle [54,55]. As cancer and chronic cardiac disease were associated with a higher mortality particularly in the Se-deficient patients, obesity was associated with a higher mortality in Zn-deficient patients and both Se-and Zn-deficiency conferred increased mortality risk in particular for diabetes patients, it is hypothesized that Se and Zn deficiency may aggravate the negative impact of cancer, obesity, chronic cardiac disease and diabetes on an adequate immune response in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study evaluated dynamic changes in albumin and lymphocytes (onCOVID inflammatory score) and found that it was independently associated with severe COVID-19. (68,69) Clinical presentation in patients with cancer is further complicated by several cancer-specific factors. For example, there have been reports that patients with cancer may have increased prevalence of asymptomatic presentation due to reflex screening practices.…”
Section: Covid-19 Presentationmentioning
confidence: 99%
“…Por lo que se debe tener un tratamiento y diagnóstico oportuno para el manejo de la estenosis, en especial de los pacientes con COVID-19 (12) ; ya que, como se mencionó, el padecer COVID-19 se relaciona con factores asociados a la estenosis traqueal sin olvidar el edema de la mucosa propiciado por la intubación, así como la ulceración, cambio tisular fibrilar e inflamación; sin olvidar que esto también se presenta asociado a los efectos propios del desarrollo de COVID-19 (13,14) .…”
Section: Discussionunclassified